Morphometry and conversion factors in the sand lobster Thenus orientalis (Lund) from Bombay waters - Kabli, L M; Kagwade, P V (Indian Journal of Fisheries, 2011)
The Sand lilbster Thenus orientalis exhibits linear relationship between carapace ler.gth and total length and between abdominal weight and total weight. The relationship is exponential in the case of total length with total weight and with abdominal weight, and of carapace length with abdominal weight.